Age‐related changes in ACL morphology during skeletal growth and maturation are different between females and males. Issue 4 (25th May 2020) - Hosseinzadeh, Shayan; Kiapour, Ata M.
Abstract: Despite a well‐established role of anterior cruciate ligament (ACL) anatomy on its biomechanics, little is known on how ACL anatomy develops and changes during skeletal growth. We hypothesized that ACL size and orientation will change by age during skeletal growth and maturation with different trends in males vs females. Magnetic resonance images of 269 unique knees (3‐18 years old; 51% female) were used to measure ACL length, cross‐sectional area, length‐to‐cross‐sectional area ratio, and elevation angles. In both males and females, ACLs became longer, thicker, and more vertical in sagittal and coronal planes by increasing age ( R 2  > 0.2; P  < .001 for all associations). ACL cross‐sectional area‐to‐length ratio increased by age only in males ( R 2  = 0.06; P  = .003). Despite similar ACL sizes between males and females at early age, adolescent males had significantly longer and thicker ACLs compared to the age‐matched females ( P  < .05). There were no sex differences in ACL elevation angles ( P  > .2) except for larger coronal elevation in 7 to 10 years old females compared to age‐matched males ( P  = .012). Observed changes in ACL cross‐sectional area‐to‐length ratio indicate that age‐ and sex‐dependent changes in ACL size are not homogenous. The trends seen in normalized ACL size measurements suggest that unlike ACL cross‐sectional area, ACL length is primarily controlled by body size. Smaller ACLs and lower cross‐sectional growth rates observed in females may be contributing factors to the higher risk of ACL injuries in females. Further investigations are required to identify the intrinsic and extrinsic factors responsible for these discrepancies.